Carbon-negative cement-bonded biochar particleboards - Liang Chen; Yuying Zhang; Claudia Labianca; Lei Wang; Shaoqin Ruan; Chi Sun Poon; Yong Sik Ok; Daniel C. W. Tsang‬ (Biochar, 2022)
Highlights Carbon-negative particleboard is  for the first time pioneered by incorporating 70 wt.% biochar. Biochar addition in MOSC systems reduced the thermal conductivity. Further incorporation of SCMs improves the mechanical properties and CO2 sequestration. Biochar particleboard can sequester 137 kg CO2 tonne−1 and yield potential profit of 92–116 USD m−3.